Intelligent elderly care - Ho, Yu Xuan (Nanyang Technological University, 2021)
As one of the most developed countries, Singapore experiences an aging population. This increasing elderly population poses a unique challenge. The fast pace of a developed country leaves insufficient time for the younger generation to provide proper elderly care. However, when left unattended, elderlies are prone to the risk of accidents, such as falling. Therefore, there is a need for a low-cost and hands-off system to monitor the elderly’s safety and well-being. The purpose of this project is to build a prototype smart device, with the use of the Internet of Things (IoT), to allow caregivers to monitor the elderly’s well-being and location in real-time. The device has functions such as heartbeat sensor, fall detector, SOS button, and transceiver for home entry status. Caregivers will be able to monitor the elderly’s well-being and whereabouts through a web server called ThingSpeak. If an abnormality is detected, a Short Message Service (SMS) will be sent to the caregiver for immediate attention.